2003
DOI: 10.1002/0471140864.ps0403s32
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Fractionation of Tissue Culture Cells

Abstract: Cell fractionation techniques include some of the most important and widely used analytical tools in cell and molecular biology, and are essential for the development of cell-free assays that reconstitute complicated cellular processes. In addition to simple gradient systems, this unit discusses the immuno-purification of organelles, in particular endosomes. As antigens, purification can be achieved using endogenous or ectopically expressed proteins, provided that appropriate antibodies are available. Alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…In order to isolate endosomes, we developed a modified immunoisolation protocol rather than using a standard subcellular fractionation technique involving high-speed centrifugation that may lead to cross-contamination of the fractions, due to the processing typically associated with postmortem tissue collection (Aniento and Gruenberg, 2003; German and Howe, 2009). In addition, we found that when using magnetic or sepharose beads, there was non-specific binding of some proteins to the beads, including PSD95.…”
Section: Discussionmentioning
confidence: 99%
“…In order to isolate endosomes, we developed a modified immunoisolation protocol rather than using a standard subcellular fractionation technique involving high-speed centrifugation that may lead to cross-contamination of the fractions, due to the processing typically associated with postmortem tissue collection (Aniento and Gruenberg, 2003; German and Howe, 2009). In addition, we found that when using magnetic or sepharose beads, there was non-specific binding of some proteins to the beads, including PSD95.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate these possibilities, we infected HeLa cells with AAV2 wt, ⌬VP1, or D9A/D13A/E17A for 16 h and prepared endosomes using floatation centrifugation in a sucrose step gradient (3,18,33). Endosomes were found enriched in fraction 6, as indicated by Western blot analysis of gradient fractions for the endosomal marker protein Rab5 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h, cells were infected with 200 viral genomes (VGs)/cell of double-iodixanol-purified AAV2 wt or AAV2 mutants in 6 ml of DMEM-i. Viruses were attached to the cells for 1 h at 4°C before the cells were shifted to 37°C, followed by incubation for 1 h. The virus was then removed, and the cells were cultivated in 15 ml of culture medium for 15 h. Early endosomal fractions were prepared as described before (3,18,33). Briefly, the cells were harvested and homogenized, and a postnuclear supernatant was prepared, adjusted to 40.6% sucrose-3 mM imidazole (pH 7.4), loaded onto the bottom of an SW60 tube, and overlaid sequentially with 35 and 25% sucrose solutions in 3 mM imidazole (pH 7. brane proteins, where they interact with adaptor proteins (AP) and thereby navigate molecular traffic, either from the plasma membrane or from the trans-Golgi network to endosomal and lysosomal compartments.…”
Section: Methodsmentioning
confidence: 99%
“…Culture media were collected and cells were then washed in 1x PBS and collected. Subcellular fractionation of BMDM cells was prepared as previously described and either RNA or protein was isolated [ 40 ]. To test the role of caspase-1, we used 250 μ M selective irreversible caspase-1 inhibitor, acetyl-Tyr-Val-Ala-Asp-chloromethylketone (Ac-YVAD-cmk) (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%